RETRACTED: Assisting Smart Construction With Reliable Edge Computing Technology - Yue, Qiang; Mu, Song; Zhang, Longguan; Wang, Zhun; Zhang, Zhonghua; Zhang, Xing; Wang, Yongge; Miao, Zhuang (Frontiers in Energy Research, 2022)
Although smart construction tools are already assisting the construction sector still a major reform are considerably seen in the coming years with Artificial Intelligence of Things (AIoT).  The purpose of this work is to develop a down to earth reliable edge computing design and plan, which can be utilized to bolster savvy development situations with tall Quality of Service. The numbers of devices connected in industrial processes is growing in tandem with the advancement of sophisticated technologies and the use of the AIoT. Big data is created as gadgets grow more integrated and need more computing power. However, as the amount of big data generated grows, processing and analytical issues arise. Cloud Computing technologies are now being used to solve processing and analytical challenges. However, using Edge Computing technologies, greater emphasis is placed on executing calculations as near to the device as feasible. As a result of these facts, this article suggests the arrangement plan, which depends on most recent cloud and computer program designing approaches and advances, and gives flexibility, interoperability and adjustment to construction companies particular needs.